The influence of the attractiveness of pineapple fruit commodity on the welfare of the people in Sipahutar District, North Tapanuli Regency - Iwan Riady (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2021)
The problem of agro-tourism development in Sipahutar District has not been able to develop, this is because it still has weaknesses, such as: 1) the district government is not yet optimal in developing the potential of the agricultural sector that can be empowered as a tourist area, 2) still inadequate tourism facilities and infrastructure such as lack of access to tourist sites, and the lack of attractions carried out 5) village road infrastructure leading to tourist areas is still dirt and gravel roads, 6) lack of promotion and information about agro-tourism areas. The purpose of this study was to analyze the influence of pineapple fruit tourist attraction on the welfare of the people of Sipahutar District and analyze the role of local governments in developing pineapple fruit commodity tourism in Sipahutar District. The analytical method used in this study is multiple regression analysis and descriptive analysis with the number of respondents as many as 94 people. The results showed that the influence of pineapple fruit tourist attraction which includes competitiveness, social capital and entrepreneurial culture has a positive and significant impact on the welfare of the people of Sipahutar District. The role of the local government in the development of pineapple fruit commodity tourism in Sipahutar District is to increase the capacity of pineapple fruit commodity business actors in Sipahutar District, North Tapanuli Regency by improving institutions, coaching, capital, and increasing the capacity of business actors.